PERSISTENT AND INTERMITTENT HYPERHYDRATION IN PATIENTS ON PROGRAM HAEMODIALYSIS: METHODS OF EVALUATION AND CORRECTION - A. G. Strokov; V. A. Terekhov; Y. L. Poz; K. N. Kryshin; Yu. V. Kopylova (Вестник трансплантологии и искусственных органов)
Hyperhydration, the sum of persistent (PH) and intermittent (IH) ones is the strong predictor of mortality in patients on program haemodialysis (PHD). The aim of this research was to investigate the complex of methods for minimization of PH as well as IH. Materials and methods. The bioimpedance multifrequency analysis (BIA), relative blood volume (RBV) monitoring and plasma conductivity evaluation by ionic dialysance device were performed in candidates for kidney transplantation. Results. In 380 PHD patients, comparing with 26 healthy persons the expansion of extracellular volume was only observed even in the cases of the huge (3.5–15 L) overload. PH of more than 15% of extracellular volume was observed in 41% of patients. The deviation of hydration status from reference value was 3.7 ± 1.4 L at first measurement and 1.9 ± 1.2 L at last one in every patient. RBV decreased insignificantly (less than 2.5% / L ultrafiltration) during PHD sessions in patients with PH. This value increased after dry weight consummation and it appeared as surrogate of intravascular refueling capacity. The minimization of sodium dialysate – plasma gradient resulted in decrease of IH. Conclusion. The elimination of both PH and IH in PHD patients is the paramount goal; it demands the complex approaches and further investigations.